Proton Pump Inhibitors Increase the Risk of Autoimmune Diseases: A Nationwide Cohort Study - Lin, Sheng-Hong; Chang, Yu-Sheng; Lin, Tzu-Min; Hu, Li-Fang; Hou, Tsung-Yun; Hsu, Hui-Ching; Shen, Yu-Chuan; Kuo, Pei-I; Chen, Wei-Sheng; Lin, Yi-Chun; Chen, Jin-Hua; Chang, Chi-Ching (Frontiers in Immunology, 2021)
Background: Previous study revealed proton pump inhibitors (PPIs) have an effect on gut microbiota. Alteration of the microbiome causes changes of the host immune system and then induces the development of autoimmune diseases (ADs). This study aimed to explore the possible association between PPIs use and ADs. Methods: This study was conducted using data from the Taiwan National Health Insurance Research Database in the period between 2002 and 2015. We performed multivariate and stratified analysis through the Kaplan-Meier method and Cox proportional hazard models to estimate the association between proton pump inhibitor use and the risk of autoimmune diseases. Results: Of the 297,099 patients treated with PPI identified, the overall mean (SD) age was 49.17 (15.63) years and 56.28% of the subjects was male. As compared with the non-PPI group, the adjusted hazard ratio (aHR) were higher for incident organ specific ADs such as Graves disease (aHR=3.28), Hashmoto thyroiditis (aHR=3.61), autoimmune hemolytic anemia (aHR=8.88), immune thrombocytopenic purpura (aHR=5.05) Henoch-Schonlein pupura (aHR=4.83) and Myasthenia gravis (aHR=8.73). Furthermore, the adjusted hazard ratio (aHR) were also higher for incident systemic ADs such as ankylosing spondylitis (aHR=3.67), rheumatoid arthritis (aHR=3.96), primary Sjogren syndrome(aHR=7.81), systemic lupus erythemtoasus (aHR=7.03). systemic vasculitis (aHR=5.10), psoriasis (aHR=2.57), systemic scleroderma (aHR=15.85) and inflammatory myopathy(aHR=37.40). Furthermore, we observed no dose-dependent effect between PPI use and the risk of ADs. Conclusions: Our retrospective population-based cohort study showed that the prescription of proton pump inhibitors is associated with a higher risk of ADs.